2006
DOI: 10.1074/jbc.m602629200
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Induces Apoptosis through the Inhibition of Proteasome Function

Abstract: Aspirin and other nonsteroidal anti-inflammatory drugs inhibit cell proliferation and induce apoptosis in various cancer cell lines, which is considered to be an important mechanism for their anti-tumor activity and prevention of carcinogenesis. However, the molecular mechanisms through which these compounds induce apoptosis are not well understood. Here we have found that aspirin treatment of the mouse Neuro 2a cells impaired the proteasome function and caused severe mitochondrial abnormalities. Treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 45 publications
8
92
0
Order By: Relevance
“…53,54,59 Recent studies have shown that MCF-7 mammospheres are insensitive to the cyclooxygenase pathway, and the COX-2 inhibitor (Indomethacin) was unable to reduce the mammosphere-forming capacity of MDA-MB-231 cells. However, these studies also showed that prostaglandin E receptor, which is a downstream regulator of COX-2 enzyme, plays critical role in regulation of stemness of BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…53,54,59 Recent studies have shown that MCF-7 mammospheres are insensitive to the cyclooxygenase pathway, and the COX-2 inhibitor (Indomethacin) was unable to reduce the mammosphere-forming capacity of MDA-MB-231 cells. However, these studies also showed that prostaglandin E receptor, which is a downstream regulator of COX-2 enzyme, plays critical role in regulation of stemness of BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin has multiple COX-independent effects and is involved in various cellular processes such as apoptosis (10,12). On one hand, aspirin induces cell apoptosis via diverse pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and animal studies have demonstrated that aspirin can induce cell apoptosis through COX-dependent and COX-independent pathways. The COX-independent effects include alteration of gene transcription (8,9), inhibition of proteasome function (10), cell cycle arrest, modulation of several protein kinases and other molecular signaling pathways (11,12) and down-regulation of nuclear factor-κB (NF-κB) activity by preventing phosphorylation and degradation of the inhibitory subunit IκB (13,14). All of these effects of aspirin are mainly observed in colon, breast and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin is commonly thought to act pharmacologically primarily via inhibition of prostaglandin synthesis (Weissmann, 1991). However, at higher concentrations, aspirin has also been shown to block NF-kB activity by directly binding to and inhibiting the kinase activity of IKKb by reducing its ability to bind ATP (Yin et al, 1998); more recently, aspirin has also been reported to inhibit proteasome activity and consequently to interfere with degradation of IkB (Dikshit et al, 2006). As such, high-dose aspirin therapy may have applications to diseases where NF-kB activity is involved, including cancer (McCarty and Block, 2006), diabetes (Yuan et al, 2001) and heart disease (Li and Fang, 2004).…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%